The Improving Vigor of White Jabon Seeds after Storage for 4.5 Years Using Gamma Ray Irradiation - M. Rahmad Suhartanto; Tatiek K. Suharsi; Evayusvita Rustam; Dede J. Sudrajat (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2018)
Low dosage gamma ray iradiation has a potency to improve the seed germination by increasing of enzimatic activities, cell division, stimulating of responsive genes to auksin and improving of seed metabolism. The aim of the research was to identify seed storability of white jabon (Neolamarckia cadamba) and to find out the effective gamma ray irradiation dosages to increase the seed vigor. Seeds were collected from 4 populations (Alas Puwo, Kampar, Batu Hijau, dan Pomalaa) and were stored for 4,5 years. Randomized completely design was used to analysis seed storability and the effect of irradiation dosages ((0, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100 Gy) on the parameters of seed germination and seedling growth. The result showed that seed storage for 4.5 years generally caused the decrease of seed viability and vigor, except for seeds from Batu Hijau.Seed moisture content decreased significantly to 4.08-4.87percent. Gamma ray irradiation provided different responses on the seed origin.Irradiation was only effetive to improve germination with an initial seed germination more than 40 percent. Overall, dose of 40 Gy was able to improve seed vigor and seedling growth so that it can be applied to increase vigor of white jabon seeds.